Calculated Tumor Volume Is an Independent Predictor of Biochemical Recurrence in Patients Who Underwent Retropubic Radical Prostatectomy - Nobumichi Tanaka; Kiyohide Fujimoto; Akihide Hirayama; Yasushi Nakai; Yoshitomo Chihara; Satoshi Anai; Atsushi Tomioka; Keiji Shimada; Noboru Konishi; Yoshihiko Hirao (Advances in Urology)
Purpose. The purpose of this study is to investigate whether the clinicopathological biopsy findings can predict the oncological outcome in patients who undergo radical prostatectomy. Materials and Methods. Between January 1997 and March 2006, 255 patients with clinically localized adenocarcinoma of the prostate (clinical T1-3N0M0) who had undergone retropubic radical prostatectomy were enrolled in this study. None of the patients received neoadjuvant or adjuvant therapy. Clinicopathological parameters were assessed to determine a predictive parameter of biochemical recurrence. Results. Of the total 255 patients, 77 showed biochemical recurrence during the follow-up period. The estimated 5-year overall survival, 5-year cause-specific survival, and 5-year biochemical recurrence-free survival rates were 97.7%, 99.5%, and 67.3%, respectively. Multivariate analysis using the Cox proportional hazards model showed that calculated cancer volume was an independent predictor among the preoperative clinicopathological parameters (𝑃<0.05). SVI and PSM were independent predictors among the postoperative parameters (SVI; 𝑃<0.001, PSM; 𝑃=0.049). Among the significant preoperative and postoperative parameters, calculated cancer volume remained an independent predictive parameter in multivariate analysis (𝑃<0.01). Conclusions. Tumor volume, as calculated by preoperative parameters, is an independent predictor of biochemical recurrence in patients who had undergone radical prostatectomy.